Adherence to Antipsychotic Drug Measured by an Arabic Version of Morisky Scale - Alhalaiqa, F.; Omari, O.; Wynaden, Dianne; Almusallami, N.; Bashtawy, M.; Morisky, D.; Batiha, A.; Alkhawaldeh, A. (2016)
2016 Copyright © Taylor & Francis Group, LLCA cross-sectional study (n = 108) was conducted to assess medication adherence levels among people with mental illness in Jordan using the Arabic version of Morisky Medication Adherence Scale. The findings showed a significant negative correlation between patients’ level of adherence, frequency of admissions, and relapses per year and a negative correlation between adherence level and frequency of follow up appointments per month. Nonadherence to antipsychotic medication in Jordan is very high and the reasons for this need to be further explored as nonadherence negatively effects the global burden of disease associated with mental illness, particularly in developing countries.